The Effect of Fatigue on the Static and Dynamic Balance in Karate Kata and Kumite Elite Men - Masoud Mirmoezzi; Heydar Sadeghi; Mahdi Jafari; Lotfali Lotfi (Biyumikānīk-i varzishī)
Objective: With regard to the effects of postural fatigue on the amount of participation in sport activities and as this may result in impaired motor functioning, the aim of this study was to investigate the effect of fatigue on static and dynamic balance in karate kata and kumite elite men. Methods: The statistical population consist of all karate kata and kumite National Karate team members in 2015-16, which involved 20 men. The sample of the study included 16 athletes with average age of 20.4 ± 23.75 years, all of whom were healthy. Static and dynamic balance was measured before and after the exercise protocol, including a severe karate training session. Static postural stability indices including mean center of pressure displacement (COP) and velocity of COP displacements (COP VEL) Direction of medial-lateral (ML) and anterior-posterior (AP), were measured in standing position on one leg. In order to evaluate the dynamic postural stability index (DPSI), the jump-landing task was used on the 1000-Hz Kistler force plate. Inferential statistics which were used to compare pre and post-test data in order to compare the effect of fatigue in kata and kumite groups at a significant level of 0.05, including paired samples t-test and covariance analysis. Results: The findings indicated that fatigue caused by intense training would significantly affect the static and dynamic balance in karate kata and kumite elite men (P<0.05). The kumite team had a better dynamic balance than the kata team (p = 0.002). Conclusion: Based on the results of the study, it can be recommended that coaches and athletes consider the negative effects of fatigue in intensive training sessions on static and dynamic balance. Since practically there is not much differences between different exercise in kata and kumite. It is recommended that the exercise program be used to delay fatigue in order to reduce the risk of musculoskeletal damage.